Barriers and facilitators of purchasing from short food supply chains: evidence from consumer focus groups in Germany, Spain, Greece and Hungary - Ágnes Szegedyné Fricz; Sophie Hieke; Constantine Iliopoulos; Irini Theodorakopoulou; Frank Jansseni; Begoña Alfaro; Débora Campos; Camille Aouinaït; Theo Benos; Elena Santa Cruz; Betty P.I. Chang; Adrienn Hegyi; et al. (International Journal of Food Studies)
This study aimed to identify the barriers and facilitators of consumers purchasing from short food supply chains (SFSC). Eight focus groups were conducted with consumers in the rural and urban areas of Germany, Spain, Hungary and Greece. Participants generally felt that increasing the convenience of purchasing SFSC products (in terms of a proximal location and being able to purchase a wide range of produce in one place) was a prerequisite for them to buy such products. Food quality in terms of taste, freshness and organic status were also taken into account in purchase decisions, and there appears to be a greater focus on health rather than the environmental implications of organic production, although the environmental aspects are also appreciated. Some participants also like the idea of supporting their local community through purchasing from local producers and/or retailers. It was believed that small-scale production and SFSC result in better quality food, but participants had less confidence in the hygiene and food safety standards of SFSC compared to longer chains. Participants thought that consumers would purchase local food if they could more easily access a variety of local food in one place, such as through supermarkets, cooperatives, farm shops and markets, or an online platform that aggregates producers.